Macro-Financial Linkages in Egypt : A Panel Analysis of Economic Shocks and Loan Portfolio Quality - Love, Inessa (IMF Working Papers; Working Paper ;, 2013)
This paper investigates macro-financial linkages in Egypt using two complementary methods, assessing the interaction between different macroeconomic aggregates and loan portfolio quality in a multivariate framework as well as through a panel vector autoregressive method that controls for bank-level characteristics. Using a panel of banks over 1993-2010, the authors find that a positive shock to capital inflows and growth in gross domestic product improves banks' loan portfolio quality, and that the effect is fairly similar in magnitude using the multivariate and panel vector autoregressive frameworks. In contrast, higher lending rates may lead to adverse selection problems and hence to a drop in portfolio quality. The paper also reports that a larger market share of foreign banks in the industry improves loan quality.